Urgensi Kewenangan Komisi Yudisial dalam Rangka Menjaga Perilaku Hakim - Dimas Yemahura Alfarauq; Siti Marwiyah; Wahyu Prawesthi (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Initially, the existence of the Judicial Commission was formed based on Law Number 22 of 2004 as a legal derivative of the institution, in article 40 paragraph (1) of Law Number 48 of 2009 concerning judicial power it is stipulated that the Judicial Commission is an external supervisory body that monitors the supervision of judges' behavior based on the code of ethics and guidelines for judges' conduct, and Law Number 18 of 2011 concerning the Judicial Commission. The legal issue of this normative legal research: What is the form of the Judicial Commission arrangement in order to maintain the behavior of judges? What is the urgency of the authority of the Judicial Commission in order to maintain the behavior of judges? The Judicial Commission is regulated in Article 24B of the 1945 Constitution, which gives the authority to propose the appointment of Supreme Court Justice and maintain the honor and conduct of judges. This authority is important to ensure that judges carry out their duties with integrity and in accordance with the applicable code of ethics. The existence of legal gaps related to the limitations of the Judicial Commission's authority in supervising the behavior of judges often makes it difficult to carry out their duties optimally. The urgency of the authority of the Judicial Commission in maintaining the behavior of judges is very important to create a judicial system that is independent, accountable, and trusted by the public. Strengthening the authority and institutional support for the Judicial Commission is needed to ensure that supervisory duties can be carried out effectively, so that the ideals of legal reform in Indonesia can be well achieved.